Undeniably Indiana : Hoosiers Tell the Story of Their Wacky and Wonderful State (Book collections on Project MUSE., 2016)
In this first crowdsourced book about Indiana, ordinary Hoosiers from all corners of the state share the eclectic, wonderful, and sometimes wacky stories that are undeniably Indiana. These true tales highlight the variety of Hoosier life: fond recollections of hometowns, legendary anecdotes of the past, Indiana's unpredictable weather, favorite foods (there's more than corn!), and chance encounters with unforgettable and infamous people. And, of course, there's always basketball. Written for anyone who has ever called this great state home, Undeniably Indiana provides the answer to the widespread question, "What is a Hoosier?"